Development strategy for ecotourism management based on feasibility analysis of tourist attraction objects and perception of visitors and local communities - Sugeng Prayitno Harianto; niskan walid masruri; Gunardi Djoko Winarno; Machya Kartika Tsani; Trio Santoso (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Harianto SP, Masruri NW, Winarno GD, Tsani MK, Santoso T. 2020. Development strategy for ecotourism management based on feasibility analysis of tourist attraction objects and perception of visitors and local communities. Biodiversitas 21: 689-698. Liwa Botanic Gardens (LBG), Lampung, Indonesia ecotourism development must be carried out as an effort to develop nature tourism with the most careful consideration in its management, without temporary benefits orientation, and the doers must have benchmarks in the process of sustainable development so that the next generation can utilize it in their time. This study aims to determine the management conditions and potential of Tourist Attraction Object (TAO) that have been operating — knowing the perceptions of tourists and local people. The method used is (i) scoring; (ii) assessing the perception of satisfaction of tourists and local people; (iii) doing intensive interviews with area managers and community leaders; (iv) identifying problems using the SWOT matrix; (v) constructing a development strategy. Data collection techniques with accidental sampling method with a total of 130 respondents based on tourist visits at the time of the study. The management of the LBG was previously managed by the Forestry Service until 2016, and in 2017 the management was handed over to the West Lampung Research and Development Agency (Balitbang). The results showed that overall, TAO gets a feasibility rating to be developed. The perception of tourists is quite satisfied with the attractions offered and the services of the manager. The community is satisfied with the ongoing management. The community wants are always to be involved in the development process. Researchers give advice on the examination of the management and marketing system in introducing the LBG to increase local and foreign tourist visitors.